(untitled) (Journal of Engineering, 2021)
There is no access to basic sanitation for half the world’s population, leading to Socioeconomic issues, such as scarcity of drinking water and the spread of diseases. In this way, it is of vital importance to develop water management technologies relevant to the target population. In addition, in the separation form of water treatment, the compound often used as a coagulant in water treatment is aluminum sulfate, which provides good results for raw water turbidity and color removal. Studies show, however, that its deposition in the human body, even Alzheimer’s disease, can cause serious harm to health and disease development. The study aims to improve the coagulation/flocculation stage related to the amount of flakes, including the absence of metal sludge formed. Initial studies were concerned with assisting and comparing natural and chemical coagulants. The key chemicals used for coagulation are aluminum sulfate (alum) and poly aluminum chloride, also known as PACL and ferric chloride.